Analisis Curse Theory pada Sumber Daya Alam Migas Bagi Warga Madura - Hidayaturrahman, Mohammad (LP2M IAIN Palangka Raya, 2018)
Government policies in natural resource management, especially in the oil and gas sector face a lot of problems. However, the government also has a responsibility to improve the life of people affected from oil and gas exploration and production activities. This research was aimed at investigating how the implementation of policies run by the central and local government toward the oil and gas management and community empowerment, especially the community located closely Â to oil and gas exploration and production activity in Madura, East Java. This research method is phenomenological research using descriptive qualitative approach. Therefore, this study is conducted through direct observation on the object during the research time. The data collection is done through observation and interview. The results of this study revealed that it is needed an integrated step done by the government, vertically, whether central, provincial, district, and village to synchronize oil and gas management and community empowerment programs. By doing so, the ideas and desires to improve the welfare and increase the state income will be realized, especially in focusing corporate and government programs improving citizenâ economic and education, whose area becomes the location of oil and gas production.